Determinants of sub-sovereign bond yield spreads – The role of fiscal fundamentals and federal bailout expectations. (December 2017) - Beck, Roland; Ferrucci, Gianluigi; Hantzsche, Arno; Rau-Göhring, Matthias
Highlights: Fiscal fundamentals and risk aversion are important drivers of sub-sovereign spreads. Within federations, bailout willingness and capacity affect sub-sovereign spreads. If the federal system allows for bailouts, markets pay less attention to fundamentals. But if the bailout capacity is constrained, fundamentals play a role in the pricing. Our results can inform the European debate about the setup of a fiscal union. Abstract: This paper investigates how bailout expectations affect the extent to which yield spreads for bonds issued by sub-sovereign entities within fiscal federations price in fundamentals related to default risk. The question is analysed both across and within federations using a novel dataset for sub-sovereign governments that includes Australian states, Canadian provinces, Swiss cantons, German Länder, US states, Spanish communities, and Indian states. The paper finds that sub-sovereign debt and deficit levels relative to GDP are important drivers of sub-sovereign spreads. However, the weight assigned by financial markets to fundamentals when pricing sub-sovereign bonds is reduced when the institutional set-up of the federation allows for bailouts. Moreover, within federations, the market's expectation of a federal bailout and the capacity of the federal government to provide support to the weaker members of the federation similarly affect the extent to which fundamental factors are priced into spreads. The paper shows that the positive link between debt and risk premia tends to break down when sub-sovereign government debt rises above certain thresholds. This could reflect the market's expectation of a federal bailout as fundamentals deteriorate. Additionally, larger sub-sovereign entities tend to pay higher premia as fundamentals worsen which could be linked to the limited capacity of the federal government to provide support as the size of the expected bailout increases. A pattern of rising risk premia as fundamentals worsen is also found for sub-sovereign entities when the central government faces borrowing constraints.